Use of Bambusa balcooa Roxb. and Bambusa tulda Roxb. in traditional bamboo gadgets of Nath-yogi’s of Sivasagar district of Assam, India - Nath, Uttam; Ao, Toshinungla; Changmai, Shamikhu; Basumatary, Nijwm (Ethnobotany Research and Applications, 2025)
Background: The present study was conducted in the Sivasagar district of Assam, India to study the traditional bamboo gadgets made from Bambusa balcooa Roxb. and Bambusa tulda Roxb. by the Nath-Yogi community. The study also aims to explore the role of the bamboo gadgets in village economy of the community. Methods: During the study, 330 individuals from 8 villages were interviewed. Along with the interviews, semi-structured questionnaires were used to obtain data. Results: Thirty four traditionally used bamboo gadgets were recorded in the study. These gadgets were used mainly in agriculture, fishing, handloom, music, and other household purposes. In 27 items, cane was used as an associated material to complete the making process. Fan tree and wood were also used in one item each. 31 items were made of Bambusa tulda Roxb. and only 3 items were made of Bambus balcooa Roxb. Conclusions: Traditional bamboo crafts made of Bambusa balcooa Roxb. and Bambusa tulda Roxb. play a crucial role in the daily life of the Nath-Yogi community in rural areas. They are ecofriendly and an indispensable part of village economy. Keywords: Nath-Yogi community, Traditional bamboo gadgets, Handloom, Ecofriendly, Village economy.